ANALISIS SIFAT PENYERAPAN AIR DAN INDEKS NYALA API PADA PAPAN KOMPOSIT YANG DI PERKUAT SERAT DAUN PANDAN DURI DAN LIMBAH SERBUK GERGAJI KAYU SENGON DENGAN RESIN POLYESTER - Bachtiar, Saiful; Sulistyowati, Emmy Dyah; Catur, Agus Dwi (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2015)
The use of composite materials as an alternative to metallic materials in the field of engineering more widespread, not only as an interior daneksterior in the automotive field but also extended to other areas such as property and architecture is to reduce the incidence of fire one only to find a replacement for wood as a raw material of houses and buildings with other alternative materials are more fire resistant, the material need not be limited in mechanical strength, but also on the physical properties. Therefore, the aim of this study was to analyze the absorption properties of water and fire index in the fiber-reinforced composite board pandanus leaves thorns and wood sawdust filler sengon with polyester resin as matriknya.Analysis of the absorption properties of the water carried by the ASTM D 5529 with a variation of the length of time of immersion (10, 20, and 30 days) and the fiber volume fraction (0%, 10%, 20% and 30%). Testing index of the flame using ASTM E1321 with long burning time of 10 minutes. To test the effect of soaking time and a fiber volume fraction of the weight gain, volume, and density on the board fiber composite pandanus thorns with 10% filler wood sawdust sengon diguanakn Two Ways Analysis Of Variance, and the effect of fiber volume fraction to index Flash Fire is used One Ways Analysis Of Variance.The results showed that the water absorption is affected by fiber volume fraction and longer soaking time. The largest percentage of water absorption occurs in the volume fraction of 30% with long soaking time of 30 days is 24.41%. Similarly, the highest percentage swelling occurs in composite board with a volume fraction of 30% with a 30-day long soaking time is 11:22% .Then the flame to the percentage of the index without fiber composite board has a greater percentage is 167.03%. By contrast the percentage of board composite index gained shortest of composite board with a fiber volume fraction of 30% ie 70.25% composite board with a fiber volume fraction of 30% also have a flame index is lower than the comparison is with wood composites sengon.